REPESENTASI KELUARGA INTI DALAM TIGA EPISODE ANIMASI KELUARGA SOMAT: SPECIAL PAK SOMAT - Stefani Ratu Lestariningtyas (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research describes Indonesian animation series of Keluarga Somat and its connection for the term of nuclear family which represented in three episodes Keluarga Somat: Special Pak Somat. This research picked three episodes of “Lomba Egrang Sekampung”, “Kue Legeslatif”, and “Diet Pak Somat”. This research explains the representation of the protagonists in this animation series and its connection with nulclear family concept. The data are collected then described with descriptive qualitative method with theory of media representation. This research aims to understand nuclear family concept which represented by Dreamtoon Animation Studios in animation series of Keluarga Somat. The conclusion for this research explains the representation of nuclear family where every family member helps each other then makes harmonious family concept.